Survival Rate and Growth Response of Humpback Grouper Seeds (Cromileptes altivelis) on Acclimatization to the Freshwater - Sonny Kristianto; Marmi Marmi; Sunaryo Sunaryo (Biota, 2019)
Successful biodiversity cultivated in freshwater fish is farmed whitefish, tiger shrimp, vannamei shrimp and. While the grouper duck (Cromileptes Mozambique) export market prospects have never tried. This research would like to know how the seed of acclimatization grouper duck into fresh water against the survival rate and growth response. Using random design complete 5 x 4 treatment, seed samples with long range 12 cm, weight 22 gr. Acclimatization of habitat in salinity of 30 ppt ppt 4. Moderate decrease in salinity 0.0 A0 is the ppt/day (controls), A0,5 (0.5 ppt/day), A1 (1 PPT/day), A1.5 (1.5 ppt/day), and A2 (2 ppt/day). Data were analyzed with the survival rate of the t test (P ≤ 0.05) the results show a decrease in salinity of 0.5 ppt/day 35% real different with controls 92.5%, but is superior than the three other treatments (A1, A1.5 and A2) dead all before reaching 4 ppt. While the growth rate data were analyzed with anova followed duncan test (P ≤ 0.05) the results show A0.5 0.60% no different with real control of 0.61% real but different (fastest) compared to three other treatments (A1, A1.5 and A2). The conclusion is grouper duck capable cultivated in brackish water 4 ppt (mesohalin) through acclimatization with decreased salinity of 0.5 ppt/day.